A three‐dimensional analysis of the development of cranial nerves in human embryos. Issue 5 (5th May 2022) - Smit, Johannes A.; Jacobs, Karl; Bais, Babette; Meijer, Berrie; Seinen, Marjolein N.; de Bree, Karel; Veldhuis, Tyas; Hagoort, Jaco; de Jong, Kees H.; Breugem, Corstiaan C.; Oostra, Roelof‐Jan; de Bakker, Bernadette S.
Abstract: To increase our understanding of the etiology of specific neurological disorders (e.g., Duane syndrome, glossoptosis in Pierre Robin sequence), proper knowledge of anatomy and embryology of cranial nerves is necessary. We investigated cranial nerve development, studied histological sections of human embryos, and quantitatively analyzed the 3D reconstructions. A total of 28 sectioned and histologically stained human embryos (Carnegie stage [CS] 10 to 23 [21–60 days of development]) were completely digitalized by manual annotation using Amira software. Two specimens per stage were analyzed. Moreover, quantitative volume measurements were performed to assess relative growth of the cranial nerves. A chronologic overview of the morphologic development of each of the 12 cranial nerves, from neural tube to target organ, was provided. Most cranial nerves start developing at CS 12 to 13 (26–32 days of development) and will reach their target organ in stage 17 to 18 (41–46 days). In comparison to the rest of the developing brain, a trend could be identified in which relative growth of the cranial nerves increases at early stages, peaks at CS 17 and slowly decreases afterwards. The development of cranial nerves in human embryos is presented in a comprehensive 3D fashion. An interactive 3D‐PDF is provided to illuminate the development of the cranial nerves in human embryos for educational purposes. This is the first time that volume measurements of cranial nerves in the human embryonic period have been presented.